Review of the book Human Displacement from a Global South Perspective: Migration Dynamics in Latin America, Africa and the Middle East - Linares Ojeda, Claudia Janet (2023)
Migration is considered a constant phenomenon enabling the exchange of traditions and construction of multicultural societies worldwide. The book Human Displacement from a Global South Perspective: Migration Dynamics in Latin America, Africa and the Middle East (2021) explains the visibility of this phenomenon through the compilation of different case studies and the integration of diverse communities due to migration. In this regard, this book analyzes the factors influencing migration, the adaptation difficulties in different contexts and the complexities currently faced by migrants. Therefore, this review aims to demonstrate the relevance and significance of migration as a field of study in the academic literature.